Uji aktivitas antibakteri fraksi n-heksana dan etil asetat daun kecombrang (Etlingera elatior) terhadap Staphylococcus aureus dan Escherichia coli - Alfi Wahyudi Nasution; Haris Munandar Nasution; Minda Sari Lubis; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Infectious diseases caused by microorganisms are diseases that are commonly found in society. The therapy used to treat infections today by administering antibiotics. However, many cases of bacterial resistance to antibiotics are caused by the irrational use of antibiotics, so is necessary to develop alternatives to antibiotics derived from plants. glycosides that can function as antimicrobials. This study aims to determine the activity of the n-hexane and ethyl acetate fractions from kecombrang leaves against Staphylococcus aureus and Escherichia coli. This research was conducted experimentally, the independent variables consisted of the ethanol extract of kecombrang leaves, n hexane and ethyl acetate fractions. The dependent variable consisted of simplicia characteristic test, kecombrang leaf phytochemical screening, antibacterial activity test of kecombrang leaf fraction against S.aureus and E.coli. Antibacterial test using n-hexane and ethyl acetate fractions made with concentrations of 10%, 30%, 50% and 70%. the positive control used the antibiotic chloramphenicol and the negative control used DMSO, and the method used was agar diffusion using paper discs.The results of the antibacterial test showed that kecombrang leaves had an inhibitory effect on Staphylococcus aureus and Escherichia coli bacteria. The inhibition power of the ethyl acetate fraction was stronger than n hexane. The strongest inhibition was found in the ethyl acetate fraction with a concentration of 30.50 and 70% against Staphylococcus aureus, namely 10.9 mm, 12.6 mm and 14.15 mm. whereas in Escherichia coli bacteria, namely 10.5 mm, 12.3 mm. and 13.9mm. and based on the CLSI inhibition zone category, 2020, the concentration fraction of 70% is in the intermediate category, concentrations of 50, 30, and 10% are in the resistant category. While the positive control is categorized as sensitive to both bacteria.